2003
DOI: 10.1210/er.2002-0033
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Local Regulation of the Growth Plate

Abstract: The growth plate is the final target organ for longitudinal growth and results from chondrocyte proliferation and differentiation. During the first year of life, longitudinal growth rates are high, followed by a decade of modest longitudinal growth. The age at onset of puberty and the growth rate during the pubertal growth spurt (which occurs under the influence of estrogens and GH) contribute to sex difference in final height between boys and girls. At the end of puberty, growth plates fuse, thereby ceasing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
347
1
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(373 citation statements)
references
References 288 publications
4
347
1
21
Order By: Relevance
“…Therefore, our results encourage the further study of rapamycin interaction with the Indian hedgehog (Ihh)/PTHrP feedback loop [27], so far not explored.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, our results encourage the further study of rapamycin interaction with the Indian hedgehog (Ihh)/PTHrP feedback loop [27], so far not explored.…”
Section: Discussionmentioning
confidence: 55%
“…Beyond providing support for growth-plate chondrocytes, the extracellular matrix is involved in the control of growth factor diffusion [27] and is linked to cartilage mineralization. The matrix structure varies in transverse and longitudinal cartilage septa [28] and, worthy of note, matrix mineralization does occur in longitudinal septa of the lower hypertrophic zone, whereas transverse septa are rarely mineralized [29].…”
Section: Discussionmentioning
confidence: 99%
“…(9) The two nuclear ERs, ERa and ERb, as well as the membrane Gprotein-coupled receptor GPR30 proposed to be an ER, are expressed in growth plate cartilage. (10)(11)(12)(13)(14)(15)(16) ERa is the main functional ER in the mouse growth plate, although ERb slightly modulates longitudinal bone growth in female but not in male mice. (17,18) We recently demonstrated that female GPR30 À/À mice displayed reduced longitudinal bone growth and reduced growth plate height that could not be reduced further by E2 treatment.…”
Section: J Jbmrmentioning
confidence: 99%
“…The inhibitory effects of GCs on growth are primarily mediated by disruption of chondrogenesis at the growth plate (8). This occurs via direct effects of GCs on chondrocyte growth and apoptosis (9,10), as well as through changes to factors such as those in the insulin-like growth factor (11) and vascular endothelial growth factor pathways (12), which disturb normal growth plate function.…”
mentioning
confidence: 99%